Mitochondrial Signaling and Hepatocellular Carcinoma: Molecular Mechanisms and Therapeutic Implications - Facciorusso, Antonio; Villani, Rosanna; Bellanti, Francesco; Mitarotonda, Domenica; Vendemiale, Gianluigi; Serviddio, Gaetano (Current Pharmaceutical Design, 2016)
Background: Molecular pathogenesis of hepatocellular carcinoma is complex and implies a multistep process involving different genetic and epigenetic alterations, as well as altered molecular pathways. Among these features, oxidative stress and mitochondria dysfunction represent an important trigger to hepatocarcinogenesis regardless of underlying liver disease etiology. An important part of the actual cancer research is focused on the molecular mechanisms and the signaling pathways involved in the process of so called “mitochondrial malignancy”. Method: Aim of this review is to summarize the main molecular mechanisms and the pathological consequences of oxidative stress and mitochondrial dysfunction in liver cancer. Furthermore, an up-to-date insight in therapeutic implications of the aforementioned processes is consistently developed. A literature search was conducted using PubMed until October 2015, based on English language journals. Results: Mitochondrial dysfunction may dramatically alter cell growth and proliferation by means of several “retrograde” mitochondria-nucleus signaling pathways, all of which have been shown to play a significant role in hepatocarcinogenesis. Nuclear oncogenes and tumor suppressors alike regulate mitochondrial turnover and function in a thick cross-talk whose role is fundamental in human oncology. Conclusion: The current knowledge on the role of mitochondrial signaling and oxidative stress in hepatocarcinogenesis seems to support the use of antioxidant agents in hepatocarcinoma patients, for instance in the adjuvant setting after radical treatments where their favorable cost-effective and safety profile may enable long-terms therapies aimed at preventing tumor recurrence. Data from randomized-controlled trials are warranted in order to confirm these promising results.
Keywords: ROS